2015
DOI: 10.1016/j.nano.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Combining magnetic nanoparticles with cell derived microvesicles for drug loading and targeting

Abstract: Inspired by microvesicle-mediated intercellular communication, we propose a hybrid vector for magnetic drug delivery. It consists of macrophage-derived microvesicles engineered to enclose different therapeutic agents together with iron oxide nanoparticles. Here, we investigated in vitro how magnetic nanoparticles may influence the vector effectiveness in terms of drug uptake and targeting. Human macrophages were loaded with iron oxide nanoparticles and different therapeutic agents: a chemotherapeutic agent (do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 47 publications
2
93
0
Order By: Relevance
“…They found that co-incubation of iron oxide nanoparticles did not influence the uptake of tPA, and tPA localized at the cytoplasm after endocytosis. This novel hybrid cell microvesicles could be manipulated by magnetic force for targeting delivery of tPA to blood clots 47 . Lately, Tadayon et al developed an extracellular biosynthesis of nanoparticles (CuNP) for the simultaneously targeted delivery of tPA and streptokinase (SK) 48 .…”
Section: Nanocarriers For Tpamentioning
confidence: 99%
“…They found that co-incubation of iron oxide nanoparticles did not influence the uptake of tPA, and tPA localized at the cytoplasm after endocytosis. This novel hybrid cell microvesicles could be manipulated by magnetic force for targeting delivery of tPA to blood clots 47 . Lately, Tadayon et al developed an extracellular biosynthesis of nanoparticles (CuNP) for the simultaneously targeted delivery of tPA and streptokinase (SK) 48 .…”
Section: Nanocarriers For Tpamentioning
confidence: 99%
“…Moreover, in some EVs-producing cells, especially primary cells, it might be difficult to achieve a satisfactory level of transgene expression, using both viral and nonviral methods of transduction. To avoid genetic manipulation, Silva et al loaded the EVs-secreting cells with iron oxide particles to produce EVs-containing magnetic nanoparticles suitable for magnetic targeting [75]. Alternatively, a series of approaches aiming at modifying the EVs after secretion, without the need of manipulating the EVs-producing cells, have been recently pursued (Figure 2).…”
Section: Targeting Extracellular Vesicles Deliverymentioning
confidence: 99%
“…Nowadays, the use of magnetic nanoparticles as drug transporters has been an area of significant interest [5]. Besides its biocompatibility, one reason for using magnetite Fe 3 O 4 nanoparticles in this type of delivery system, is given by the possibility of applying any of the previously mentioned targeting approaches: passive by EPR [6], and active by magnetic targeting [7,8,9,10] or specific functionalizing [11,12,13,14]. Fe 3 O 4 nanoparticles have been already used as carriers for GEM in some in vitro approaches aiming to improve the drug release time [15], and efficiency [16,17].…”
Section: Introductionmentioning
confidence: 99%